Laser-Induced Synthesis of Electrocatalytically Active Ag, Pt, and AgPt/Polyaniline Nanocomposites for Hydrogen Evolution Reactions - Vasileva, Anna A. A.; Mamonova, Daria V. V.; Petrov, Yuri V. V.; Kolesnikov, Ilya E. E.; Leuchs, Gerd; Manshina, Alina A. A. (Nanomaterials, 2023)
We present an efficient and easily implemented approach for creating stable electrocatalytically active nanocomposites based on polyaniline (PANI) with metal NPs. The approach combines in situ synthesis of polyaniline followed by laser-induced deposition (LID) of Ag, Pt, and AgPt NPs. The observed peculiarity of LID of PANI is the role of the substrate during the formation of multi-metallic nanoparticles (MNP). This allows us to solve the problem of losing catalytically active particles from the electrode's surface in electrochemical use. The synthesized PANI/Ag, PANI/Pt, and PANI/AgPt composites were studied with different techniques, such as SEM, EDX, Raman spectroscopy, and XPS. These suggested a mechanism for the formation of MNP on PANI. The MNP-PANI interaction was demonstrated, and the functionality of the nanocomposites was studied through the electrocatalysis of the hydrogen evolution reaction. The PANI/AgPt nanocomposites demonstrated both the best activity and the most stable metal component in this process. The suggested approach can be considered as universal, since it can be extended to the creation of electrocatalytically active nanocomposites with various mono- and multi-metallic NPs.
CRIS-Team WoS Importer:2023-01-27